Critical review of religion in coping against the COVID-19 pandemic by former COVID-19 muslim patients in Malaysia - Ab Rahman Z.; Kashim M.I.A.M.; Mohd Noor A.Y.; Saari C.Z.; Hasan A.Z.; Ridzuan A.R.; Ashaari M.F.; Kassim S.B.M.; Norhayati Rafida Abdul Rahim (Innovare Academics Sciences Pvt. Ltd, 2024)
Indexed by Scopus